KURANGNYA PENDIDIKAN REPRODUKSI DINI MENJADI FAKTOR PENYEBAB TERJADINYA PELECEHAN SEKSUAL ANTAR ANAK - Simbolon, Dewi Fiska (Kopertis Wilayah X, 2018)
Equity education in Indonesia is a very complicated issue. The inequality of education in Indonesia occurs in the layers of the poor. Factors affecting inequality is caused by financial or financial factors The higher the level of education, the more expensive costs incurred by individuals. Indonesia is a developing country where most of its people live at an insufficient level. There are many cases of child sexual abuse, where the perpetrator is predominantly an adult and most are the immediate family of the victim, but there are cases of the child. This can be proved by the existence of reports of complaints of victims who enter to the authorities. Criminal acts of child sexual abuse are issues that require special attention by the government as they relate to the morality of the nations generation. In this case the court is an institution or institution related to the child as the perpetrator of acts of pidan especially in sexual crimes. Any child who is a victim or perpetrator of sexual violence or who is dealing with the law is entitled to be kept secret. Every child victim or offender is entitled to legal aid and other assistance